Evaluating Learning Management System (LMS) Effectiveness: An LPOMR Model Approach - Supiani Supiani; Dedy Achmad Kurniady; Thutju Yuniarsih; Nur Aedi (Pedagogia: Jurnal Ilmiah Pendidikan, 2024)
The purpose of this study is to evaluate the use of Learning Management System (LMS) as a school management model to improve the quality of education. This study uses the Research and Development (R&D) method with the ADDIE approach, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Through this approach, LMS is evaluated to measure its effectiveness in supporting school management and improving the education process. The findings of the study indicate that the implementation of this LMS has improved coordination between schools, teachers, students, and parents, which has led to increased community involvement in school activities and decision making. This increased involvement has contributed significantly to improving the quality of education. This study provides valuable insights into creating a more efficient and participatory school management system through the application of digital technology.